THE ROLE OF COMMUNITY HEALTH CADRES IN PREVENTIVE AND PROMOTIVE MEASURES FOR MATERNAL AND NEONATAL EMERGENCIES - Seventina Nurul Hidayah; Reny Eka Saputri; Riska Arsita Harnawati (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
The maternal and neonatal periods are highly vulnerable stages that require proper monitoring and timely health interventions to prevent serious complications, such as postpartum hemorrhage, infections, or emergency conditions in newborns. Data from the Tegal Regency Health Office in 2024 indicate that preventive and promotive services at posyandu are suboptimal, with postpartum maternal visit coverage at 58%, below the 80% national target. This highlights the importance of the active role of posyandu cadres in providing education, conducting monitoring, and assisting mothers and infants. This study aims to identify the role of posyandu cadres in preventive and promotive efforts related to maternal and neonatal emergencies in Slawi Wetan Village. This descriptive qualitative study involved five cadres and four postpartum mothers. Data from interviews and observations were analyzed thematically. Results show cadres educate on danger signs of pregnancy, conduct home visits, and remind mothers of schedules via communication media. Supporting factors include health center support and community enthusiasm, while obstacles include limited time availability of cadres and uneven awareness among mothers. In conclusion, posyandu cadres play an important role in improving preparedness and promotive maternal and neonatal health. However, cross-sectoral support and capacity building for cadres are still needed to achieve optimal health services.